Quality of life and associated factors amongst older adults in a remote community, Nepal - Saurav Chandra Acharya Samadarshi; Pimsurang Taechaboonsermsak; Mathuros Tipayamongkholgul; Korravarn Yodmai (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of the study is to assess the quality of life (QOL) of older adults and explore factors associated with it. Design/methodology/approach - A cross-sectional study was conducted in a remote community in Nepal. A total of 671 older adults aged 60 years were enrolled in the study. QOL was measured by WHOQOL-OLD questionnaire. Data were analyzed using multiple logistic regression. Findings - Most participants were female (53.0%), illiterate (70.6%), married (64.2%) and living with family (59.3%). Among participants, 82.4% had fair QOL, and the autonomy domain received the lowest score (average = 10.98). After adjusting the model, the elderly aged <70 years had 11.07 times better QOL (aOR = 11.070; 95% CI = 2.546-48.123), elderly with high sufficient income had 2.73 times better QOL (aOR = 2.738; 95% CI = 1.183-6.337) and elderly free from depression had 9.45 times better QOL (aOR = 9.452; 95% CI = 3.466-25.773) compared to their counterparts. The elderly receiving social support had 9.97 times better QOL than those who did not (aOR = 9.976; 95% CI = 3.152-31.574), and those able to afford healthcare services had 4.69 times better QOL than those who could not afford it (aOR = 4.694; 95% CI = 1.046-21.063). Originality/value - The five predictors - age, income sufficiency, depression, social support and healthcare service affordability - were found to significantly affect QOL. This study suggests special care strategies for vulnerable older adults addressing the issues that affect geriatric depression. This article provides relevant information to the government to consider increment of income, encourage family and community for social support and make health services affordable for older adults.